2018
DOI: 10.1177/0194599817753609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Balloon Dilation and Laser Eustachian Tuboplasty in Patients with Eustachian Tube Dysfunction: A Meta‐analysis

Abstract: Objective We aimed to perform a meta-analysis examining balloon dilatation and laser tuboplasty for the treatment of eustachian tube dysfunction (ETD). Data Sources PubMed, Cochrane, and Embase search up to April 18, 2016, with the following keywords: eustachian, middle-ear, eustachian tuboplasty, balloon tuboplasty, laser tuboplasty, laser dilatation, and balloon dilatation. Review Methods Randomized controlled trials and prospective, retrospective, and 1-arm studies of patients with ETD treated with balloon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Some groups reported that 66–72% of patients achieved normal middle ear aeration following laser tuboplasty at 1 year [ 2 4 ]. Although balloon tuboplasty has some advantages, such as a short operation time, good tolerability, lack of mucosal injury of the anterior tubal wall and significant complications, as well as improvements in long-term subjective and objective measures [ 6 9 ], Wang et al [ 21 ] reported that Valsalva maneuver results were similar between the balloon and laser procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups reported that 66–72% of patients achieved normal middle ear aeration following laser tuboplasty at 1 year [ 2 4 ]. Although balloon tuboplasty has some advantages, such as a short operation time, good tolerability, lack of mucosal injury of the anterior tubal wall and significant complications, as well as improvements in long-term subjective and objective measures [ 6 9 ], Wang et al [ 21 ] reported that Valsalva maneuver results were similar between the balloon and laser procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of prospective and retrospective studies comparing Eustachian tube balloon dilatation and laser Eustachian tuboplasty in Taiwan showed no inferiority of Eustachian tube balloon dilatation results, but also noted the need for further studies to assess its efficacy. 17…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this systematic review are in line with some of the previously published literature, demonstrating little evidence about Laser Eustachian tuboplasty or Microdebrider Eustachian tuboplasty as a treatment for adult Eustachian tube dysfunction. 4,5 On the contrary, the findings of all studies reporting Laser and Microdebrider Eustachian tuboplasty as an effective treatment are in 6 This recent review analysed 13 uncontrolled studies dealing with 1063 patients. 6 This review concluded improvement in the symptoms of Eustachian tube dysfunction with the use of Balloon dilatation and Laser Eustachian tuboplasty.…”
Section: Comparison Of the Findings Of This Review With The Previousl...mentioning
confidence: 99%
“…4,5 On the contrary, the findings of all studies reporting Laser and Microdebrider Eustachian tuboplasty as an effective treatment are in 6 This recent review analysed 13 uncontrolled studies dealing with 1063 patients. 6 This review concluded improvement in the symptoms of Eustachian tube dysfunction with the use of Balloon dilatation and Laser Eustachian tuboplasty. 6 But this conclusion was based on low-level evidence.…”
Section: Comparison Of the Findings Of This Review With The Previousl...mentioning
confidence: 99%